Setting the Tolerance and Action Limit for Patient-specific Quality Assurance of Craniospinal Irradiation Volumetric Modulated Arc Therapy: Based on AAPM TG-218 Report - Sathiya Raj; Sathiyan Saminathan; Kiruthika Prakasam (Journal of Medical Physics)
Purpose: The purpose of this study was to investigate the tolerance limits (TL) and action limits (AL) in gamma passing rate for craniospinal irradiation volumetric modulated arc therapy (VMAT) treatment plans. Materials and Methods: Twenty-eight patients were planned using the VMAT technique; plans were delivered on an Elekta Versa HD. The delivered fluence was recorded by PTW 2D array, and the gamma passing rate (%GP) was analyzed using PTW VeriSoft. The universal TL and AL from TG 218 were applied to analyze the %GP for each plan. As per AAPM TG 218, a statistical process control of %GP was performed to set the TL and AL. Results: The average %GP for the brain, upper spine, and lower spine was 98.4%, 98.8%, and 98.4%, respectively. The TL and AL for the brain, upper spine, and lower spine were TL: 95.1%, 95.1% and 94.8%, and AL: 89.7%, 89.3%, and 86.7%, respectively. The analysis of variance test showed that the P value in %GP among the brain, upper spine, and lower spine was >0.1679. The %GP rate between the sites was not statistically significant. Conclusion: AAPM TG 218 guidelines are more suitable for establishing TL and AL for craniospinal irradiation (CSI) VMAT plans. This study suggests that a single value of TL and AL for CSI plans, rather than site-specific values, could be suitable for monitoring CSI patient-specific quality assurance trends and the same can be utilized.